1985
DOI: 10.1148/radiology.156.2.4011890
|View full text |Cite
|
Sign up to set email alerts
|

Lead arthropathy: arthritis caused by retained intra-articular bullets.

Abstract: The cases of 14 patients seen 6 weeks to 7 years after gunshot wounds with painful, restrictive joint disease and retained intra-articular bullets were reviewed. Twelve patients had radiographic findings characteristic of lead synovitis. The earliest finding was a fine, punctate deposition of radiopaque lead on the articular cartilage that resembled chondrocalcinosis but was of greater density. This was followed by more discrete lead speckling of hypertrophied synovium. The opacities became larger, coarser, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…However, all authors agree that the arthroscopic removal of foreign body and joint lavage after sustaining an injury is a safe and useful method to help prevent further complications (mechanical disorder, chronic synovitis and infection) (4,5,12).…”
Section: Discussionmentioning
confidence: 99%
“…However, all authors agree that the arthroscopic removal of foreign body and joint lavage after sustaining an injury is a safe and useful method to help prevent further complications (mechanical disorder, chronic synovitis and infection) (4,5,12).…”
Section: Discussionmentioning
confidence: 99%
“…Intra-articular debris has potential to develop septic arthritis and lead toxicity [62][63][64][65][66][67][68][69]. Tornetta and Hui arthroscopically evaluated 33 gunshot injuries to the knees and found a 42 % incidence of meniscal damage and 15 % incidence of cartilage damage all in the absence of radiographic evidence [37].…”
Section: Antibiotics and Debridement For Low-velocity Joint And Pelvimentioning
confidence: 99%
“…Damage to the articular architecture and the presence of loose bodies have potential to create a shift in weight-bearing dynamics with subsequent acceleration of arthritis. Although rare, systemic lead toxicity can result because synovial fluid acts as a lead solvent leading to non-specific symptoms of fatigue, anemia, headaches, peripheral neuropathy, abdominal pain, and encephalopathy as systemic lead concentrations rise [62][63][64][65][66][67][68][69]. In light of such articular damage, potential for loose bodies, and risks for local infection and systemic plumbism, the literature suggests articular irrigation and debridement [36-38, 39••, 40].…”
Section: Antibiotics and Debridement For Low-velocity Joint And Pelvimentioning
confidence: 99%
“…Of those, 48 were Level V evidence, reducing the count to seven studies; hand searching the bibliographies of these yielded one additional study. The final number of studies included in this review therefore was eight, including seven Level IV studies (case series) [1,2,11,15,19,22,28] and one Level III study (retrospective study with a control group) [30] (Table 1).…”
Section: Search Strategy and Criteriamentioning
confidence: 99%
“…Sclafani et al [28] reported a retrospective case series of 14 patients with retained intraarticular bullets. Patients were seen at between 6 and 7 weeks from injury.…”
Section: Selected Indications For Bullet Removalmentioning
confidence: 99%